1999
DOI: 10.1042/bj3440775
|View full text |Cite
|
Sign up to set email alerts
|

Proteophosphoglycans of Leishmania mexicana: Identification, purification, structural and ultrastructural characterization of the secreted promastigote proteophosphoglycan pPPG2, a stage-specific glycoisoform of amastigote aPPG

Abstract: Protozoan parasites of the genus Leishmania secrete a range of proteophosphoglycans that appear to be important for successful colonization of the sandfly and for virulence in the mammalian host. A hallmark of these molecules is extensive phosphoglycosylation by phosphoglycan chains via the unusual linkage Manα1-PO % -Ser. In this study we have identified and purified to apparent homogeneity a novel proteophosphoglycan (pPPG2) which is secreted by Leishmania mexicana promastigotes (sandfly stage). Amino acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…There are several possible explanations for the evident surface binding, but limited detection, of internal H2A in amastigotes. First, it is known that amastigotes resemble the lpg1 Ϫ promastigotes in that they lack LPG1 but retain PPG (18) and that the structure of the glycans found on amastigote PPG in L. mexicana differs considerably from the simpler LPG-like linear PG polymers found on promastigote PPG (17,21). These unique structures may allow interaction with histones but limit their translocation.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible explanations for the evident surface binding, but limited detection, of internal H2A in amastigotes. First, it is known that amastigotes resemble the lpg1 Ϫ promastigotes in that they lack LPG1 but retain PPG (18) and that the structure of the glycans found on amastigote PPG in L. mexicana differs considerably from the simpler LPG-like linear PG polymers found on promastigote PPG (17,21). These unique structures may allow interaction with histones but limit their translocation.…”
Section: Discussionmentioning
confidence: 99%
“…1995, 1996, 1999 a ; Gopfert et al 1999; Klein et al . 1999; Ilg, 2000). No such characterization of PPG has been reported in the case of L. donovani .…”
Section: Introductionmentioning
confidence: 99%
“…Since LPG seems to be absent from L. donovani amastigotes, PPG may play the important functions attributed to LPG in attachment of the parasites to host macrophages (Ilgoutz and McConville, 2001). PPG is a product of both promastigotes (pPPG) and amastigotes (aPPG) as observed in the case of L. mexicana and L. major, the causative organisms for cutaneous leishmaniasis (CL), and has been demonstrated to have species and stage-specific functions (Ilg et al 1995(Ilg et al , 1996Gopfert et al 1999 ;Klein et al 1999 ;Ilg, 2000). No such characterization of PPG has been reported in the case of L. donovani.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale driving this research has been that these protozoan parasites are likely dependent on secretion of effector molecules into the host extra- and intracellular environments for initiation and maintenance of successful infection. This theory is based on investigations of individual secreted proteins (Vannier-Santos et al, 1995 ; Hubel et al, 1997 ; Klein et al, 1999 ; Joshi et al, 2002 ; Lieke et al, 2008 ; Gomez et al, 2009 ; Halle et al, 2009 ; Silverman et al, 2010b ; Jaramillo et al, 2011 ) and proteins mechanistically involved in the secretion pathway (Besteiro et al, 2006 ), which showed reduced virulence after loss of protein function or secretion. It has been known for some time that these eukaryotic organisms use a classical secretion pathway for the proper dissemination of newly translated proteins throughout the cell and it has been thought that this pathway was the route to the cell surface (McConville et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%